Effect of Plant Debris Removal on the Incidence of Rice Sheath Blight Disease in Bangladesh - Parveen, S; Hossain, MS; Ali, MA; Ali, MA (Bangladesh Rice Journal, 2019)
Sheath blight caused by Rhizoctonia solani is a major disease of rice (Oryza sativa L.) in Bangladesh that affects the crop in almost every season. The effect of floating debris removal on the incidence of sheath blight was assessed from the previously infected fields of three upazilas of Rajshahi district during T. Aman 2010. Each field was divided into two plots. Floating debris were removed from one plot while the other plot remained unremoved. Percent hill infection was higher in control plots from where floating debris were not removed (FDNR) than that of FDR plots from where floating debris were removed from the fields of Tanore, Godagari and Paba at 35 days after transplanting. The percent hill infection was 8.89% in FDR plots and 56.67% in FDNR in Tanore with a difference of 47.78%. Maximum 63.01% reduction in hill infection was found in Tanore between FDR and FDNR, whereas significant reduction in hill infection was found in Godagari (46.75%) at maximum tillering stage. The reduction in the incidence of sheath blight was 51.08% in Paba at maturity stage due to removal of floating debris from the field before transplanting. The average yield of three fields was 4.79 t ha-1 in FDR plot, whereas in FDNR, it was 4.18 t ha-1 in Tanore. Thus there was an yield difference of 0.61 t ha-1 in between FDR and FDNR plots. However, there was negative relationship between tiller infection and grain yield of rice. It is evident that the regression equation that the grain yield was 6.75 t ha-1 in the FDNR plots when there was no infections but infection in the tillers reduced the grain yield by 0.41 unit for every unit increase in tiller infection. Bangladesh Rice j. 2018, 22(1): 83-90